Health behavior knowledge among Hispanic California islanders: Evaluation of a parental educational intervention. Issue 1 (19th February 2019) - Parsons, Karla; Rutkowski, Elaine M.; Turel, Ofir
Abstract: Purpose: To evaluate the impact of a school nurse‐led pilot parent‐focused education program for healthy eating and physical activity to reduce childhood obesity. Design and Methods: A quasi‐experimental intervention design was used to assess the knowledge of 11 Hispanic mothers regarding healthy food choices and physical activity over a period of 1 year. Results: There was an improvement in parental knowledge domains. Children's body mass index (BMI) stabilized at the 1‐year follow‐up in the intervention group, while the BMI increased in the nonintervention group. Outcomes included improvement in parental health knowledge and children's BMI. Practice Implications: Pediatric and school nurses have a powerful role in preventive education. Knowledge gained by identifying the benefits of healthy food choices and physical activity for Hispanic mothers of obese children can be transformed into lifestyle changes for their children's weight control that begins in the home.